Constraining ring rolling of thin-walled conical rings with transverse ribs. (15th July 2022) - Tian, Duanyang; Han, Xinghui; Hua, Lin; Wang, Xiaokai; Chen, Fei
Highlights: A novel constraining ring rolling process (CRR) is proposed to manufacture thin-walled conical rings with inner transverse ribs (TWCRITR). A mechanical model for predicting metal flow in CRR of TWCRITR is established and validated. Three new metal flow modes in CRR of TWCRITR are found based on the established mechanical model. The mechanisms behind three metal flow modes are revealed based on the established mechanical model. Abstract: As critical load-bearing components of aerospace equipment, thin-walled conical rings with inner transverse ribs (TWCRITR) are widely used for manufacturing rocket body, aircraft fuselage and space station shell et al., due to light weight, high strength and high load-bearing capacity. However, TWCRITR cannot be manufactured by traditional ring rolling (TRR), due to thin skin and high ribs. Aimed at this problem, a novel constraining ring rolling method (CRR) is proposed in this work to achieve the near-net-shape manufacturing of TWCRITR with high performance and efficiency. CRR innovatively uses a constraint roll and two baffles to fully constrain the diameter and height enlargement of ring, which ensures that the CRR process is still stable and the metal is enforced to flow axially to form high and wide ribs. Owing to the extreme geometry of TWCRITR and the complicated constraints of rolls in CRR of TWCRITR, the inherent relation between geometric and process parameters, stress state and metal flow is complicated, and it cannot be quantitatively determined by the FE simulation or experiment. Hence, the mechanical model which can determine the quantitative relation between geometric and process parameters, stress state and metal flow in CRR of TWCRITR is firstly established by using the slab method and upper bound method. Secondly, three new metal flow modes related with rib width in CRR of TWCRITR are found based on the established mechanical model. The first one is that the real-time height difference of two ribs slightly fluctuates and the two ribs almost grow synchronously when the width of two ribs is almost identical. The second one is that the rib with small width at the small end grows much faster than the rib with large width at the large end when the width difference of two ribs exceeds a critical value. The third one is that the rib with small width at the large end grows much faster than the rib with large width at the small end when the width difference of two ribs exceeds a critical value. Further, the quantitative relations between the metal flow resistance, divided-flow plane and rib growth under three metal flow modes are revealed theoretically, and consequently the mechanisms behind three metal flow modes in CRR of TWCRITR are clarified theoretically. Finally, the simulation and experiment for CRR of TWCRITR are conducted, and TWCRITR with 3 mm in skin thickness, 7 mm in rib width and 12.5 mm in rib height (the ratio of rib height to skin thickness is 4.16 and the ratio of rib width to skin thickness is 2.33) are stably rolled. Moreover, the roundness of rolled TWCRITR is good (it nearly approaches the inner surface roundness of constraint roll). The predicted values of rib height using the established mechanical model are in good accordance with the simulated and experimental ones, which validates the established mechanical model. Through analyzing the novel CRR process and complicated metal flow mechanisms, it is demonstrated that CRR is promising for manufacturing TWCRITR with high performance and efficiency. Graphical abstract: Image, graphical abstract